La complejidad de un campo social específico - Ringuelet, Roberto Ricardo; Rey, María Inés (2008)
El objetivo principal de este texto es exponer los aspectos generales y algunas conclusiones de un proyecto de investigación y desarrollo sobrela Región Rural Periurbana de La Plata. Entendida como un complejo campo social específico en el marco del periurbano. Se desarrollan brevemente: la historia regional, cuestiones de enfoque teórico, la construcción económica y política de la región y el campo de relaciones sociales interculturales
The main aim of this text, is to provide the general aspects and some conclusions of a project of investigation and developmen appear on the Periurban Rural Region of La Plata. Understood like a complex specific social field within the framework of the periurban area. They are developed briefly: Regional history, questions of theoretical approach, the economic and political construction of the region and the field of intercultural social relations
Keywords: Desarrollo territorial; Campo social; Territorial development; Social field; Antropología cultural y social; Desarrollo económico y social